La extinción del derecho de alimentos y los derechos del alimentante - Ortiz Parra, Johanna Elizabeth (2023)
ABSTRACT The main purpose of this research study was to focus on the right to maintenance or (child support) which allows people to claim from the person obliged to provide them with sustenance for their benefit, these beneficiaries being children and adolescents who are minors, who are studying or who have a disability, which is why the objective of this research was to carry out a legal and doctrinal analysis of the form of extinction of the right to maintenance by the provisions of the Organic Code of Childhood and Adolescence and the Constitution of the Republic of Ecuador, in order to determine the forms of processing used by judges and the legal effects that they cause. The methodology used in this research project was the inductive-deductive method, as a research technique a survey was applied to a population of ten lawyers in free practice where it was shown that the right to food in Ecuador is governed by a series of laws, Among them the Civil Code, COPEG, Organic Code of Childhood and Adolescence, among others, being these laws the ones that reveal the reasons for which the right to food is extinguished, concluding that the right to food guarantees that the rights of both parties are adequately protected throughout the process.